An update on Hong Kong's exchange of information developments and engaging with BEPS. Issue 2 (3rd July 2017) - Sawyer, Adrian
ABSTRACT: The Hong Kong Special Administrative Region (HKSAR) implemented automatic exchange of information (AEOI) with the Inland Revenue (Amendment) (No. 3) Ordinance 2016 coming into effect on 30 June 2016. This development is one of the latest phases in the reform of the HKSAR's exchange of information capability, and is an important issue as AEOI 'challenges' the HKSAR's approach to privacy of information. AEOI follows earlier legislative reform to permit the HKSAR to enter into tax information exchange agreements (TIEAs), and the signing of a Model 2 intergovernmental agreement (IGA) under the United States' (US's) Foreign Account Tax Compliance Act (FATCA). The HKSAR has been actively engaged in the Group of Twenty (G20)/Organisation for Economic Co-operation and Development's (OECD's) Base Erosion and Profit Shifting (BEPS) initiative, particularly as an Associate Member that has enabled it to facilitate implementation of the relevant BEPS Action Plans in both the HKSAR and internationally. Collectively AEOI and BEPS have 'opened up' the HKSAR to greater international scrutiny and will introduce greater complexity into the HKSAR's tax system. This paper briefly reviews the historical developments in information exchange in the HKSAR, focussing on the implications of AOEI and BEPS developments for the HKSAR, with some preliminary thoughts as to what the future may look like for businesses operating in the HKSAR.